KASUS NEWMONT (Pencemaran di Teluk Buyat) - Lutfillah, Kiki (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2011)
Newmont’s Case is one of many corporate crimes happened in Indonesia. Investment policy by government which gives concession to foreign investor to exploit Indonesian natural source has brought impact to human safety and surrounding environment system as well, as what happen to citizen in Teluk Buyat coast. Indonesian government failure to ask the responsibility from Newmont Minahasa Raya Company shows the weakness of State position when facing foreign corporation. In the name of ‘investment climate’, they can press a country to cancel law process that is done. Precious lesson from Newmont’s case can be used by government to prevent and minimize negative impact and maximize positive impact at once from mining companies’ activities in Indonesia.